Factors influencing recurrence following anatomic lung resection for clinical stage I non-small cell lung cancer. (February 2019) - Schuchert, Matthew J.; Normolle, Daniel P.; Awais, Omar; Pennathur, Arjun; Wilson, David O.; Luketich, James D.; Landreneau, Rodney J.
Highlights: Recurrence following resection for clinical stage I lung cancer ranges from 20 to 40%. Recurrence is predominantly dictated by adverse pathological characteristics. Risk factors include tumor size, grade, inflammation and angiolymphatic invasion. Extent of resection (segment vs. lobe) does not appear to impact on recurrence risk. Abstract: Objectives: Anatomic lung resection provides the best opportunity for long-term survival in the setting of early-stage non-small cell lung cancer (NSCLC). However, 20–30% of patients develop recurrent disease following complete (R0) resection for Stage I disease. In the current study, we analyze the impact of patient, surgical and pathologic variables upon recurrence patterns following anatomic lung resection for clinical stage I NSCLC. Patients and methods: A total of 1132 patients (384 segmentectomies, 748 lobectomies) with clinical stage I NSCLC were evaluated. Predictors of recurrence were identified by proportional hazards regression. Differences in recurrence patterns between groups are illustrated by log rank tests applied to Kaplan-Maier estimates. Results: A total of 227 recurrences (20.0%) were recorded at a median follow-up of 36.8 months (65 locoregional, 155 distant). There was no significant difference in recurrence patterns when comparing segmentectomy and lobectomy. Multivariate analysis demonstrated that angiolymphatic invasion, tumor size, tumor grade and the presence of only mild-moderate tumor inflammation were independent predictors of recurrence risk. Conclusions: Recurrence following anatomic lung resection is influenced predominantly by pathological variables (tumor size, tumor grade, angiolymphatic invasion, tumor inflammation). Optimization of surgical margin in relation to tumor size may improve outcomes. Extent of resection (segmentectomy vs. lobectomy) does not appear to have an impact on recurrence-free survival when adequate margins are obtained.